2008
DOI: 10.1071/fp07197
|View full text |Cite
|
Sign up to set email alerts
|

Two separate UV-B radiation wavelength regions control expression of different molecular markers in Arabidopsis thaliana

Abstract: Fluence-response curves were obtained at nine wavelengths in the interval 280–360 nm for mRNA transcripts of four molecular markers induced by ultraviolet-B (UV-B) radiation in Arabidopsis thaliana (L.) Heynh.: CHS (encoding chalcone synthase), PDX1.3 (encoding an enzyme involved in formation of pyridoxine), MEB5.2 (encoding a protein with unknown function but which is strongly upregulated by UV-B), and LHCB1*3 (encoding a chlorophyll a/b binding protein). Intact Arabidopsis plants were irradiated for 3 h usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
2
21
1
Order By: Relevance
“…There are several examples in the literature that tempts one to speculate that plant UV-B signaling may proceed via several routes. These include peak induction of gene expression and production of UV-absorbing pigments in response to distinct wavelengths within the UV-B range and responses that still occur in cop1 and uvr8 seedlings where the UVR8-mediated UV-B signaling pathway is abolished (Ulm et al 2004, Brown and Jenkins 2008, Kalbina et al 2008, Safrany et al 2008, Gardner et al 2009, Shinkle et al 2010, Leasure et al 2011, Lang-Mladek et al 2012. A recent report also indicated that pyrimidine dimers formed under UV-B in DNA may signal to stress-activated MAP kinase signaling (Gonzalez Besteiro and Ulm 2013).…”
Section: Are There Additional Plant Uv-b Photoreceptors?mentioning
confidence: 99%
“…There are several examples in the literature that tempts one to speculate that plant UV-B signaling may proceed via several routes. These include peak induction of gene expression and production of UV-absorbing pigments in response to distinct wavelengths within the UV-B range and responses that still occur in cop1 and uvr8 seedlings where the UVR8-mediated UV-B signaling pathway is abolished (Ulm et al 2004, Brown and Jenkins 2008, Kalbina et al 2008, Safrany et al 2008, Gardner et al 2009, Shinkle et al 2010, Leasure et al 2011, Lang-Mladek et al 2012. A recent report also indicated that pyrimidine dimers formed under UV-B in DNA may signal to stress-activated MAP kinase signaling (Gonzalez Besteiro and Ulm 2013).…”
Section: Are There Additional Plant Uv-b Photoreceptors?mentioning
confidence: 99%
“…Our results indicate that in the presence of high UV-A irradiance, UVR8 may have dual functions in regulating the UV-B gene expression response. We show that UVR8 had a negative role in the transcript accumulation of genes involved in the UVR8-dependent pathway (HY5 and SIG5; Brown and Jenkins, 2008), genes regulated by UVR8 independently from HY5 (SPS; Brown et al, 2005), and genes induced in response to UV-B, such as MEB5.2 (Brosché et al, 2002;Kalbina et al, 2008), RUP2 (Gruber et al, 2010), and At5g01520 (Oravecz et al, 2006). Interestingly, most of these genes are also regulated at the transcription level by either UV-A or blue light (Supplemental Fig.…”
mentioning
confidence: 98%
“…the pdx1.3 mutant is derepressed in PR-5 expression. Also, the UV-B-dependent downregulation of the photosynthetic LHCB1 * 3 gene is considerably smaller in pdx1.3, partially blocking signalling from the putative UV-B receptor absorbing radiation in the 280e290 nm waveband which controls expression of another subset of UV-B-regulated genes [39], including LHCB1 * 3.…”
Section: Discussionmentioning
confidence: 99%
“…6 the knowledge regarding UV-B regulation of the PDX1 and pyridoxine levels and their influence on other UV-regulated genes. Transcription of the PDX1.3 gene is accomplished by low level UV-B radiation in the waveband between 300 and 310 nm [39] by a putative UV-B receptor. This receptor would regulate PDX1.3 expression via the UVR8 and COP1 components since corresponding mutants lack UV-B induction of PDX1.3 (Ref.…”
Section: Discussionmentioning
confidence: 99%